(untitled) (Asian Journal of Medical and Biological Research, 2021)
The cyclin dependent kinase (CDK) inhibitors have recently been found to be of potential use as anticancer drugs. The present research work focuses on screening of compounds targeting multiple pathways involved in human cancers along with CDK-regulated cell cycle for prospective anticancer potential. Molecular docking study of selected compounds were performed to determine the binding affinity of selected compounds towards respective targets of cancer cells to verify if there is any physical interaction of these inhibitors with their reported target proteins as claimed in the existing literatures. Prior to docking, molecular pathway prediction and gene set enrichment analyses were performed to identify the target molecules by using appropriate bioinformatics tools. Interestingly, the results of in silico molecular docking have been found to be in line with the laboratory findings that are obtained from the literatures. Specifically, few of our selected CDK inhibitors, namely Abemaciclib, Palbociclib, AMG 925 and RGB 286638 showed good binding scores against BCL2, TS, mTOR in addition to CDKs (4, 6 and 9). On the basis of scientific evidence based on published scholarly articles and according to molecular docking results, it can be inferred that these CDK inhibitors as anticancer agents may play a very promising role in cancer treatment and can be used as potential lead compounds for the development of target therapy against human cancers. However, more intensive research is needed to confirm the feasibility of these compounds to be used in treating cancer and it is expected that this work will provide a stimulating impetus for the development of chemotherapeutic agents in future. Asian J. Med. Biol. Res. 2021, 7 (2), 126-131